Applying the Reduced Differential Transform Method to Solve the Telegraph and Cahn-Hilliard Equations: Mahmoud S. Rawashdeh, Nazek A. Obeidat - Team, Support (Thai Journal of Mathematics, 2015)
In this paper, we apply the Reduced Differential Transform Method (RDTM) to solve two Physics models of nonlinear partial differential equations (NLPDEs) such as, Telegraph equation, Cahn-Hilliard equation, and two nonhomogeneous NLPDEs equation. The study outlines the significant of the method and the results showed that the method reduces the numerical calculations. The examples we present in this paper reveals that the proposed method is very effective, simple and can be applied to other nonlinear partial differential equations models in the area of Mathematical Physics and Engineering.